The Effect of E-Service Quality and E-Trust on E-Customer Loyalty in the Bank Syariah Indonesia (BSI) Mobile E-Banking Application with E-Customer Satisfaction as an Intervening Variable (Case study on BSI customers in Bandar Lampung) - Rizkya, Yunita Anggraini; Putri, Rosydalina (International Journal of Economic, Business & Applications, 2024)
This study aims to analyze and prove the effect of E-Service Quality and E-Trust on E-Customer Loyalty in the e-Banking application of Bank Syariah Indonesia (BSI) Mobile with E-Customer Satisfaction as an Intervening variable this study there are problems at the level of use of BSI Mobile continues to increase, fraud cases, and service quality problems electronic (e-service quality) in BSI Mobile services where there are obstacles from the bank that is less responsive and less responsive. This study uses a quantitative approach using primary data and data collection by distributing questionnaires. The sample determinant uses Lemeshow formula so that the sample required is 100 respondents and the type of nonprobability sampling. Alat dalam menganalisis data adalah Structural Equation Modeling-Partial Least Square (SEM-PLS) dengan alat bantu software SmartPLS versi 4.0.Hasil penelitian menunjukkan bahwa E-Service Quality tidak berpengaruh signifikat terhadap E- Customer Loyalty ,E-trust berpengaruh positif dan signifikat terhadap E-Customer Loyalty.E-service Quality berpengaruh positif terhadap E-Customer Satisfaction .E-trust berpengaruh positif dan signifikat terhadap E-Customer Satisfaction .E-Customer Satisfaction berpengaruh positif dan signifikat terhadap E-Custumer Loyalty. E-Customer Satisfaction mampu memediasi hubungan positif dan signifikan antara  E-Service Quality terhadap E-Loyalty. E-Customer Satisfaction mampu memediasi hubungan positif dan signifikan antara E-Trust terhadap E-Loyalty